Treatment of Epileptic Encephalopathies: Current State of the Art. (January 2018) - Nariai, Hiroki; Duberstein, Susan; Shinnar, Shlomo
Childhood epileptic encephalopathies are age-dependent disorders of the brain whose hallmarks include loss of neurologic function over time, abnormal electroencephalographic findings, and seizures. Ictal and interictal electrographic activity are conjointly thought to be at the root of the often devastating neuropsychological deterioration, which is specific to the maturing brain. The goals of treatment are not only to control seizures, but also to prevent or reverse neurologic loss of function. In general, time is of the essence in diagnosis, and experienced specialists should promptly design a treatment plan. Hormonal and immune therapies are at the forefront of treatment in many cases, with traditional antiepileptic drugs and surgery (when an identifiable lesion is present) playing a limited role. However, gold standard evidence for treatment of epileptic encephalopathies remains limited. Ongoing clinical and basic research may lead to better understanding of these catastrophic conditions and to better and more effective therapies.